A simplified model for dynamic analysis of the indoor thermal environment of rooms with a Chinese kang. (January 2017) - Gao, Xiangxiang; Liu, Jiaping; Hu, Rongrong; Akashi, Yasunori; Sumiyoshi, Daisuke
Abstract: This paper uses thermodynamics equilibrium theory to develop a mathematical model for dynamic thermal processes pertaining to rooms with a Chinese kang (a heatable brick bed). The model is developed through analysis of the dynamic thermal equilibrium of indoor air temperature and the temperature of interior and exterior surfaces of the building envelopes of rooms with a kang . It is developed and solved using a thermal reaction coefficient. Based on data from a field test, a simplified mathematical model of thermal processes in such a room is presented. The model only takes into account the radiation heat transfer between the exterior surface of the kang 's faceplate and the other interior surfaces of the building envelope, while ignoring the reciprocal radiation heat transfer between all other interior surfaces. A simplified mathematical model pertaining to the Chinese kang is also put forward. This model does not take into account the reciprocal radiation heat transfer between the interior surfaces of the Chinese kang . By combining these two models, the hourly values pertaining to indoor air temperature and exterior temperature of the kang 's faceplate can be predicted for different burning modes of the Chinese kang . MATLAB was used for calculating the target temperatures and solving the thermal reaction coefficient. The model was validated by error analysis and correlation analysis, the result of which shows that this mathematical model can accurately predict various characteristics concerning the temperatures in a room with a Chinese kang . Highlights: The research target is not only kang itself, but more the room with a kang. A calculation method is developed on basis of the thermodynamics equilibrium theory. The model that we built is validated in practice by error analysis and correlation analysis.